PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS CABAI RAWIT (Capsicum frutescens L) - Lavenia Mamahit; Jantje Pongoh; A.G. Tulungen; Paula C.H. Supit (Universitas Sam Ratulangi, 2017)
ABSTRACT This research aims to understand growth and the production of several varieties chili ( Capsicum frutescens L ) that have been carried out in the village Kauneran One subdistrict Sonder for seven months from May until December 2015. The research used random design complete with three varieties treatment namely Taruna, Genie, and Nirmala. Variable observed that is observation age flowering, flowering plants as high, tall plant during harvest time, age harvest, with a heavy fruit, heavy of a fruit without stalk, heavy of a fruit without stalk and seeds, the number of fruit. Using data analyzed test F if there is continued influence treatment by test different real smallest ( LSD ) 5%. The results of the study obtained age flowering of a plant chili the average age flowering from to three varieties chili subjects not markedly dissimilar. Average height plants as flowering, obtained varieties taruna produce average height the highest plants followed varieties genie and the lowest are varieties niramala. Tall plant at harvest varieties taruna has the average highest and the lowest are varieties nirmala. Age harvest the fastest in varieties nirmala followed varieties genie and varieties taruna. Total with a heavy fruit, shows that varieties taruna yields heavy fruit with a highest followed varieties niramala and heavy fruit lowest are varieties genie. Total heavy of a fruit without stalk varieties taruna is the highest followed varieties nirmala lowest varieties genie. Varieties taruna total heavy of a fruit without stalk and seeds highest, followed varieties nirmala and the lowest are varieties genie. Varieties genie produce the average number of fruit highest followed varieties nirmala and the lowest varieties taruna. Based on the research has done inferred varieties taruna has tall plant and weights fruit chili the heaviest, while varieties nirmala having age flowering and the days of crop genjah, and varieties genie obtained the number of fruit most. Of the result of this research suggested can be tested back on land / embankment to get the characteristic appearance of growth and the production of more maximum between varieties. Keywords : Chili, Varieties